Understanding Mud Volcano System Using Hele-Shaw (H-S) Experiment: Seismic Confirmation at East Java Mud Volcano - Muhammad Burhannudinnur; Dardji Noeradi (Journal of Geoscience, Engineering, Environment, and Technology, 2021)
Numerous researchers have carried out studies on the mud volcano system in East Java. However, there have been no experiments on the mud volcano system's mechanism, including overpressure confirmed by direct subsurface data. Therefore, this study aims to directly evaluate the mud volcano system's mechanism using the Hele-Shaw (H-S) experiment with the subsurface data confirmation. The H-S experiment utilized four primary materials: quartz sand diameter below 250 µm and 320 µm to analogize the porous layer. Gypsum flour clay is the ductile layer, while mud from the Kuwu and Kesongo Mud Volcanoes is the original material from nature. Wax represents impermeable material. The sealing layer is made of wax, and oxygen represents the natural fluids of the rock formation. The overpressured zone is created by pumping oxygen into a layer of quartz sand covered by a wax as an impermeable layer. Pressure is measured digitally, and the process is continuously recorded to produce traceable data. Each material was experimented on individually to determine the critical phase characteristics, valve fault structure geometry, and validation with seismic interpretation. The results indicate that the critical phase of the mud volcano system is characterized by the dome structure at the surface, with high intensify of gas and oil seepage. Piercement structure geometry is shown by plumbing of fluidization zone, which becomes shallower than before. Furthermore, each material's piercement structure geometry shows a consistent pattern, with differences in the density of the fault and pressure structures. Thus, the H-S experiment's validation with seismic interpretation shows a similar geometry in pressure structures and valve faults as the mud volcano system's migration paths.